Surgical Treatment for Ruptured Abdominal Aneurysm - Yamazato, Ario; Yamada, Tomoyuki; Takaba, Kiyoaki (Japanese Journal of Cardiovascular Surgery, 2002)
Elective resection of abdominal aortic aneurysms is now a safe operation, but mortality related to ruptured abdominal aortic aneurysm (rAAA) remains high. In many reports, there has been much discussion about the factors that affect the mortality rate of patients who had rAAA repair. Preoperative shock is the most frequently cited prognostic factor related to survival. At the induction of anesthesia in these patients it is not rare for hypotension to cause deep shock. To prevent these deep shock states, we make a mid-abdominal skin incision simultaneously at the induction of general anesthesia just after preparation. Forty-four cases of rAAA underwent emergency surgery with this technique between April 1993 and December 1999. We also reviewed medical records of these 44 consecutive patients to evaluate clinical factors in mortality after rAAA resection. The overall hospital mortality rate was 18.2% (8/44) in our series. Factors associated with poor prognosis were the duration of preoperative shock state (p=0.031), an episode of cardiac arrest (p=0.015), an episode of loss of consciousness (p=0.018), systolic blood pressure of less than 60mmHg at the induction of anesthesia (p=0.019), intraperitoneal rupture (p=0.010) and intraoperative massive blood transfusion (p=0.043). These findings suggest that these factors may be reflections of preoperative shock and intraoperative technical errors. The surgical results of rAAA have improved significantly due to the prevention of hypotension which may cause a state of deep shock at induction of anesthesia. Although the patient's outcome after rupture of AAA is partly determined before intervention by the surgeon, efforts for rapid diagnosis and prompt flawless surgery can increase survival.